Rehabilitation for traumatic brain injury - High, Walter M. (OUP E-Books., 2005)
Presents a review of the effectiveness of rehabilitation interventions. This work includes evidence-based reviews of specific areas of brain injury rehabilitation, critiquing the methodoligical problems of studies in the area, and then outlining directions for research.